South-North microfaunal exchanges in Africa - (:unkn) unknown (My University, 2018)
All along the Quaternary period, North Africa experienced several climate changes and different waves of dispersal of faunas from Europe, southwestern Asia and sub-Saharan Africa, especially during wetter periods allowing the vegetation of the Sahara. Several species of tropical affinity were sporadically recorded in North Africa during the Pleistocene, and the present paper aims to bring a global overview of the Quaternary South-North exchanges concerning microvertebrates, in taking the particular example ofArvicanthis.This rodent genus is now frequenting sub-Saharan savannas, but has made punctual incursions into North Africa at key periods for human history. We highlight the importance to review ancient and recent North African collections having yielded Arvicanthis (and other tropical species) in order to precise their specific attribution, their origin, their relationship with the current populations, and to propose ways of thinking about the way and timing of faunal and human dispersal events under climatic influence.
Keywords: African Research